24.64%‐Efficiency MA‐Free Perovskite Solar Cell with Voc of 1.19 V Enabled by a Hinge‐Type Fluorine‐Rich Complex. (1st January 2023) - Li, Zhijun; Wu, Meizi; Yang, Lu; Guo, Kunpeng; Duan, Yuwei; Li, Yong; He, Kun; Xing, Yifan; Zhang, Zheng; Zhou, Hui; Xu, Dongfang; Wang, Jungang; et al.
Abstract: High density of defects at interface severely affects the performance of perovskite solar cells (PSCs). Herein, cobalt (II) hexafluoro‐2, 4‐pentanedionat (CoFAc), a hinge‐type fluorine‐rich complex, is introduced onto the surface of formamidinium cesium lead iodide (FACsPbI3 ) film to address the issues of perovskite/Spiro‐OMeTAD interface. The existence of CoFAc passivates both organic cation and halide anion vacancies by establishing powerful hydrogen bonds with HC(NH2 )2 + (FA + ) and strong ionic bonds with Pb 2+ in perovskite films. In addition, CoFAc serves as a connecting link to enhance interfacial hole‐transport kinetics via interacting with Spiro‐OMeTAD. Consequently, FACsPbI3 PSCs with CoFAc modification display a champion power conversion efficiency (PCE) of 24.64% with a charming open‐circuit voltage ( V OC ) of 1.191 V, which is the record V OC among all the reported organic‐inorganic hybrid PSCs with TiO2 as electron transport layer. Furthermore, CoFAc‐modified devices exhibit an outstanding long‐term stability, which can maintain 95% of their initial PCEs after exposure to ambient atmosphere for 1500 h without any encapsulation. Abstract : A hinge‐type fluorine‐rich complex cobalt (II) hexafluoro‐2, 4‐pentanedionat (CoFAc) is developed to optimize the interface of FACsPbI3 /Spiro‐OMeTAD, which can passivate both organic cations and halide anion vacancies on perovskite surface, and enhance interfacial hole‐transport kinetics by interaction with Spiro‐OMeTAD. Consequently, CoFAc‐modified FACsPbI3 solar cells yield a respectable PCE of 24.64%, a record V oc of 1.191 V, and excellent stability.